Glosa do uchwały Sądu Najwyższego z dnia 17 lutego 2016 r., sygn. III CZP 111/15 - Różowicz, Konrad (Studia Prawa Publicznego, 2019)
Glosa do uchwały Sądu Najwyższego z dnia 17 lutego 2016 r., sygn. III CZP 111/15